Petrarkos recepcija Lietuvoje - Ulčinaitė, Eugenija (Literatūra, 2015)
The article addresses the problem of the Lithuanian reception of the works of the major poet of the Italian Renaissance Francesco Petrarca (1304–1374). Lithuanian humanists of the 16th and the 17th centuries, such as Petrus Roysius, Andreas Volanus as well as the poet Mathias Casimirus Sarbievius, are known to have been in possession of the works of Petrarch. There seems to be no doubt that Lithuanian poets and intellectuals of the 19th and 20th centuries must have been familiar with Petrach’s works, at least with his famous Sonnets. Nevertheless the article states that a wider circle of Lithuanian readers is only vaguely familiar with Petrarch’s works as very few sonnets by Petrach and only several fragments of his Latin works have been translated into Lithuanian.